PENGARUH LAYANAN DIORAMA TERHADAP KEPUASAN PENGGUNA DI DINAS KEARSIPAN DAN PERPUSTAKAAN PEMERINTAH KABUPATEN BADUNG - Wulansari, Ni Kadek Desi; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT This research is a descriptive quantitative study that aims to determine the effect of diorama services on user satisfaction in the Archives and Badung District Government Library if measured by the ServQual method. Data collection techniques are by distributing questionnaires that are calculated using a Likert scale using five independent variables, namely: physical evidence or tangibles, reliability, responsiveness, assurance, empathy, and one The dependent variable is user satisfaction. The sampling technique used was purposive sampling. The analysis technique used in this study is simple regression analysis. Hypothesis testing results show that the calculated t value is smaller than alpha, it can be concluded that there is an influence of diorama services on user satisfaction in the Archives Service and the Government Library of Badung Regency. Keywords: ServQual, Library Service, Diorama Service, User Satisfaction